REALISASI PENGAJARAN BAHASA ARAB MELALUI MEDIA AUDIO VISUAL PADA MAHASISWA CLUB BAHASA ARAB IAIN PONTIANAK - Hidayat, Moh Yusuf (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
This research aimed to determine the form of Arabic language learning realization through audio visual media on Arabic club students in IAIN Pontianak. It focused on the Arabic learning materials and whether this activity can improve the competence of Arabic club students in learning Arabic language which is expected on KKNI Arabic language for university. This research used qualitative approach using descriptive data through interview from informants in IAIN Pontianak. The result revealed that Arabic language learning realization through audio visual media on Arabic club students carried out by mentors in IAIN Pontianak is not more than the realization of learning pattern which determine on the implementation of the Arabic lesson plan and syllabus, and than the materials taught has referred to the standard of competence expected in university on KKNI Arabic language, and teaching realization can measure the competence of Arabic club students expected in university on KKNI Arabic language. Keywords: Arabic Language, Audio Visual Media, IAIN Pontianak